Advancing the coral propagation toolkit via hypersalinity induced coral micropropagates - Walton, Emily; Badder, Lindsey; Galindo-Martínez, Claudia Tatiana; Berry, David B.; Tresguerres, Martin; Wangpraseurt, Daniel (Frontiers in Marine Science, 2024)
In the face of escalating threats posed by human-induced climate change, urgent attention to coral reef restoration is imperative due to ongoing reef degradation. Here, we explored the potential of generating coral micropropagates as a tool to rapidly generate coral tissue for reef restoration and reef engineering. We developed a hypersalinity-induced polyp bailout protocol and a simple attachment device to support the growth of micropropagates on commonly used restoration substrates. We found that hypersalinity induction, at a rate of < 1 ppt hr -1 , produced healthy micropropagates of the coral Stylophora pistillata. The highest attachment success (~74%) was achieved in CaCO3 substrate devices, which outperformed PVC (~48%) and Portland cement (~5%). Settled micropropagates displayed rapid growth rates on both CaCO3 (0.037 mm²/day ± 0.002 SE) and PVC (0.057 mm²/day ± 0.008 SE) substrates, while Portland cement induced tissue degradation. Our study provides a detailed methodology for reliably generating, attaching, and growing coral micropropagates and underscores the potential of polyp bailout as a viable technique supporting coral propagation efforts.